Hi!
Simplify: (–8) • (6) – (5) • (–2)
Using PEMDAS
Multiplication
(when you multiply two negatives, you get a positive,
when you multiply one negative and a positive, you get a negative)
-8 * 6 = -48
-5 * -2 = 10
-48 + 10
Subtraction
(imagine a number line)
-48 - 10 = -38
Simplify: (–4) • (9) – (5) • (–2)
Multiplication
-4 * 9 = -36
-5 * -2 = 10
-36 + 10
Subtraction
-36 - 10 = -26
Evaluate 4(a – 3b) when a = –4 and b = 6.
Put in the values, then solve.
4(-4 - 3 * 6)
Solve using PEMDAS
4(-4 - 18)
4 * -22 = -88
Evaluate 5(a – 2b) when a = –3 and b = 5.
5(-3 - 2 * 5)
5(-3 - 10)
5 * -13 = -65
The answers are
-38
-26
-88
-65
Hope this helps! :)
-Peredhel